2011
DOI: 10.1371/journal.pntd.0000925
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Geography of Plague Transmission Areas in Northeastern Brazil

Abstract: Plague in Brazil is poorly known and now rarely seen, so studies of its ecology are difficult. We used ecological niche models of historical (1966-present) records of human plague cases across northeastern Brazil to assess hypotheses regarding environmental correlates of plague occurrences across the region. Results indicate that the apparently focal distribution of plague in northeastern Brazil is indeed discontinuous, and that the causes of the discontinuity are not necessarily only related to elevation—rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 24 publications
(37 reference statements)
1
28
0
1
Order By: Relevance
“…They have different epidemiological characteristics and patterns of disease manifestations in the human population. The foci have alternating periods of high incidence followed by other periods of low incidence or even the absence of cases (Baltazard, 2004;Giles et al, 2011). The presence of similar genotypes separated by long geographical and temporal distances as in the A 2 and B 2 subgroups remains to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…They have different epidemiological characteristics and patterns of disease manifestations in the human population. The foci have alternating periods of high incidence followed by other periods of low incidence or even the absence of cases (Baltazard, 2004;Giles et al, 2011). The presence of similar genotypes separated by long geographical and temporal distances as in the A 2 and B 2 subgroups remains to be explained.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with those of Baltazard 29 , who considered that the geographical massifs of Ibiapaba, Baturité, Machado, Uruburetama, Pedra Branca and Matas constitute a single focus. Giles et al 30 confirmed that plague is focal in northeast Brazil, with a discontinuous distribution. These studies showed that those foci depend on a broad set of conditions, and are not necessarily correlated with their elevation, but likely to the presence of the hairy-tailed bolo mouse, Necromys lasiurus, which is the primary plague host in these foci, and is responsible for epizootics.…”
Section: Yearmentioning
confidence: 96%
“…First the Porto city, in Portugal, was attacked by the disease, after that, some neighbors' countries of the South America, like Paraguay and Argentina, and, finally, Santos, in São Paulo coast, where, for the first time in history, the disease landed in national field, in October of 1899 [12,17].…”
mentioning
confidence: 99%
“…Since that time, all of the foci entered a period of relative inactivity, with few or no human cases [17], concentrated in Bahia, being the last register, in this state, in Feira de Santana city, in 2000. After a silent period of four years, the Ceará registered the last case of the country in Pedra Branca city, in 2005 [19].…”
mentioning
confidence: 99%